Prosody and Corpora - Heliana Mello; Amina Mettouchi; Marianne Mithun; Alessandro Panunzi; Tommaso Raso (Cadernos de Linguística, 2021)
This paper focuses on the experience of spoken corpora compilation and discusses the relevance of prosody in this type of endeavor, as well as in the study of spoken language in its several possibilities. Through the voices of scholars associated with four different projects (CorpAfroAs, Mohawk Corpus, LABLITA, C-ORAL-BRASIL), the steps considered of utmost relevance in both the compilation and research potential of spoken corpora are presented; additionally, perspectives for the field in the future are pointed out.